Integrasi Islam Dan Ilmu Pengetahuan - Ika, Ika; Sufitriyani, Sufitriyani; Sobah, Siti Diyaus; Febiyani, Hilda (STAI Denpasar Bali, 2023)
Integrating religious knowledge with general knowledge is a longstanding problem, but along with the development of scientific skills in all fields, the integration of science is the key to success in the world of Islamic education and makes Islam the mecca of science, this opens up a wide range of opportunities to integrate science. Universally, science can be classified into three: natural sciences, social sciences, and humanities. the three sciences are actually rooted in an integrated foundation of science, namely the Qur'an and hadist, showing, communicating the existence and attributes of god and everything that happens in the universe through its verses. Science is a collection of knowledge that will be gained through human efforts to understand the world and its surroundings. The dichotomization of science in the western concept did not last long because it was increasingly clear that the progress of science led to one source, namely Allah SWT. So we can conclude that although religion and science are different, however, it does not mean that these two things cannot be integrated, because both religious knowledge and science all come from Allah SWT.